Anders Carlson: capstone - Carlson, Anders, artist (Colorado State University. Libraries, 2016)
The artist's statement: My work explores the relationship between traditional print design and digital media. With influences such as Michael Beirut and Aaron Draplin, beautiful graphic solutions to complex problems are a thread throughout my work. Ever since I was a child I have been fascinated by the psychology of others. What may start as a simple visual design can sometimes become a part of who we are and how we think. I believe it is a designer's job to care deeply for the people who will interact with our work because it will somehow affect their life. Through this kind of work, a designer learns how to make the space for themselves and the people around them to intentionally create the life they would like to have. It starts with an idea that can be communicated through a visual means, and becomes a means of reinventing the world and ourselves. My focus on branding and web projects for clients in the Fort Collins area represents my belief that this kind of work can affect the world in a massive way. This tool of visual design can empower people or harm them; I choose to try to make dreams come true, both my own, and the generous people who have enlisted my help on various projects.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design